Effect of nonsteroidal anti-inflammatory drugs on the inflammatory response of bovine endometrial epithelial cells in vitro - M.A. Crookenden; A.V.R. Lake; C.R. Burke; J.T. Pratt; M.D. Mitchell; C.V.C. Phyn; J.R. Roche; A. Heiser (Journal of Dairy Science, 2023)
ABSTRACT: Chronic postpartum uterine infection detrimentally affects subsequent fertility. Nonsteroidal anti-inflammatory drugs (NSAID) are used to alleviate pain and treat inflammatory conditions in transition dairy cows with varying success. To screen the efficacy of NSAID in the absence of animal experiments, we have established an in vitro model to study uterine inflammation. Inflammation was induced in cultured bovine endometrial epithelial cells by challenging cells with an inflammation cocktail: lipopolysaccharide and proinflammatory cytokines, interleukin-1β (IL1β) and tumor necrosis factor α (TNFα). Release of the inflammation markers, serum amyloid A (SAA) and α-1-acid glycoprotein (αAGP), was measured by ELISA. Concentration of these markers was used to indicate the effectiveness in dampening inflammation of 5 NSAID: meloxicam, flunixin meglumine, aspirin, ketoprofen, and tolfenamic acid. Three NSAID, meloxicam, flunixin meglumine, and tolfenamic acid, were successful at dampening the release of SAA and αAGP into cell-culture supernatant, and the corresponding treated cells were selected for down-stream mRNA expression analysis. Expression of 192 genes involved in regulation of inflammatory pathways were investigated using Nanostring. Of the genes investigated, 81 were above the mRNA expression-analysis threshold criteria and were included in expression analysis. All SAA genes investigated (SAA2, SAA3, M-SAA3.2) were upregulated in response to the inflammation cocktail, relative to mRNA expression in control cells; however, AGP mRNA expression was below the expression analysis threshold and was, therefore, excluded from analysis. Treatment with NSAID downregulated genes involved in regulating chemokine signaling (e.g., CXCL2, CXCR4, CXCL5, and CXCL16) and genes that regulate the eicosanoid pathway (e.g., LTA4H, PTGS2, PLA2G4A, and PTGDS). Of the 5 NSAID investigated, meloxicam, flunixin meglumine, and tolfenamic acid are recommended for further investigation into treatment of postpartum uterine inflammation. The results from this study confirm the immunomodulatory properties of the endometrial epithelium in response to inflammatory stimuli and suggest that NSAID may be beneficial in alleviating uterine inflammation.